EARLY STUDY OF BIOCHARCOAL QUALITY FROM POULTRY LIVESTOCK WASTE - Anggorowati, Dwi Anna; Minah, Faidliyah N.; Artayani, Anis; Mustiadi, Lalu (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2020)
Bio charcoal is one type of fuel in the form of charcoal made from various kinds of biological or biomass material, which includes agricultural waste, forestry waste, agro-industrial waste, animal waste from livestock waste. Bio charcoal is produced from the carbonization process or the charcoal process of materials containing carbon (biomass). One of the biomass that has the potential to be used as raw material for bio charcoal is poultry manure originating from poultry livestock waste. The composition of poultry livestock waste (chicken manure) is crude protein by 9.97-12.67% and crude fiber by 30.36-32.65. This study aims to determine the optimal carbonization temperature and particle size in the carbonization process so that optimal Fixed Carbon level can be obtained by using variations in the size of Chicken Manure Particles, namely: 30 mesh, 40 mesh, 50 mesh, and Charcoal temperature: 200, 225, 250, 275 and 300° C. Stages of the process carried out is drying chicken manure to the weight of constant chicken manure (water content < 10%) and then mashed and sieved to sizes of 30, 40, and 50 mesh and the last stage is the charcoal process of chicken manure with variations in temperature of 200, 225, 250, 275, and 300° C until the perfect charcoal process. From this study, the best parameter is obtained at 350° C and 50 mesh particle size with 45% Fixed Carbon content, 3.26% moisture content, 41% ash content, and volatile matter content 22%.